2014
DOI: 10.1186/s12934-014-0151-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic basis of laboratory evolution of butanol tolerance in photosynthetic Synechocystis sp. PCC 6803

Abstract: BackgroundRecent efforts demonstrated the potential application of cyanobacteria as a “microbial cell factory” to produce butanol directly from CO2. However, cyanobacteria have very low tolerance to the toxic butanol, which limits the economic viability of this renewable system.ResultsThrough a long-term experimental evolution process, we achieved a 150% increase of the butanol tolerance in a model cyanobacterium Synechocystis sp. PCC 6803 after a continuous 94 passages for 395 days in BG11 media amended with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…In the previous study, we developed an optimized protocol characterizing the time-series metabolic responses for metabolite isolation and MS analysis, and achieved identification of more than 65, 60 and 111 chemically classified metabolites from Escherichia coli [26], cyanobacterium Synechocystis sp. PCC 6803 [31], and heterotrophic dinoflagellate microalga Crypthecodinium cohnii [32], respectively. In this study, we followed the similar protocol with minor modification by collecting the cells under light and dark culture at day 4, 7 and 9.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous study, we developed an optimized protocol characterizing the time-series metabolic responses for metabolite isolation and MS analysis, and achieved identification of more than 65, 60 and 111 chemically classified metabolites from Escherichia coli [26], cyanobacterium Synechocystis sp. PCC 6803 [31], and heterotrophic dinoflagellate microalga Crypthecodinium cohnii [32], respectively. In this study, we followed the similar protocol with minor modification by collecting the cells under light and dark culture at day 4, 7 and 9.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the possible synergistic effects for combinations of the effective chemicals were also investigated. To determine the mode of action (MOA), metabolomics that has been demonstrated as a valuable tool in analyzing cell metabolism in various microalgae was applied (Su et al, 2014;Wang et al, 2014), and the results revealed the possible metabolic basis for the stimulatory effects of the SA & ETA and the BNOA & ETA combination on lipid accumulation in C. cohnii.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the two batches of supernatants were merged and stored at -80°C (Wang et al 2014b). Analysis was performed on an Agilent 1260 series binary high-performance liquid chromatography (HPLC) system (Agilent Technologies, Waldbronn, Germany) and an Agilent 6410 triple quadrupole mass analyzer equipped with an electrospray ionization (ESI) source and controlled by the Agilent Mass Hunter workstation liquid chromatography with triple-quadrupole (LC/QQQ) acquisition software (version B.04.01).…”
Section: Biofilm Growth On a Steel Surfacementioning
confidence: 99%